Sustitución parcial de la leche cruda fluida de bovino por leche cruda fluida de cabra, para incrementar los sólidos totales para la elaboración de queso fresco - Valladares Torres, Franz Leonardo (2015)
In this research work the partial substitution of raw bovine milk fluid with raw goat milk was carried out in order to increase the total solids in the manufacture of cheese at the Pilot Dairy Plant of the Punzara Experimental Farm belonging to the National University of Loja. For this research three treatments were conducted: Treatment 1 was a mixture of 50% cow's milk and 50% goat milk; treatment 2 was carried out using a mixture that was 60% cow's milk and 40% goat’s milk and Treatment 3 used a 70% cow's milk and 30% goat's milk mixture. Five repetitions for each treatment were implemented using a total of 90 liters of goat milk and 150 liters of cow's milk. The evaluation of the parameters comprised: a physical-chemical analysis of the cow's milk, a physico-chemical analysis of the goat´s milk and yield, as well as a respective quality control of the milk, analysis of the temperature, the pH, the acidity and density. The output yield milk / cheese in T1 was 2.44 kg from 15.67 kg of milk therefore this was the best conversion average; in T2 from 15.68 kg of milk 2.35kg of cheese was obtained and in T3 from 15.74 kg of milk 2.36 kg of cheese was acquired. In the physical-chemical analysis of both cow's milk and goat's milk, the values obtained were within the technical parameters for each of the species.